Obesity Care and Bariatric Surgery - Murayama, Kenric M.; Kothari, Shanu N. (World Scientific, 2016)
The intent of the book is to provide readers with a summary of the obesity problem with specific focus on the metabolic health issues (ie, diabetes mellitus), obstructive sleep apnea, non-alcoholic fatty liver disease and the psychological effects of obesity. This will provide readers with an understanding of the commonly performed operations for obesity along with evidence-based outcomes, nutritional issues, and metabolic consequences.